DEL MICROSCOPIO A LA MEDICINA MICROBIANA - Gómez Gutiérrez, Alberto; Departamento de Microbiología de la Facultad de Ciencias e Instituto de Genética Humana en la Facultad de Medicina, Pontificia Universidad Javeriana, Bogotá (2004)
The invention of the microscope, in contrast with many other instruments in the history of science, and similarly only to the telescope, resulted in the  creation of a new science: microbiology. The technical development of this barroque instrument, such as happened with the violin, revealed complex  worlds in quest of human understanding. In this article we present a  cronological perspective of the main turning points that finally put the once rare instrument in the center of the medical diagnosis at the end of the firstmillennium AD of our culture..